Geographic Information System Searching Locations for Hospital and Police Offices Based on Android - Junafan, Achmad (Institute of Computer Science (IOCS), 2024)
Currently the technology is growing rapidly. Using geographic information systems and media services internet navigation system or GPS (global positioning system) which is present on the platform android smartphone, google maps and google services that is product of virtual map, free and online. Where the public can access the map anywhere and anytime when needed. But the google map does not show the location of police stations and hospital as a whole therefore the need for the development of graphic information system (GIS) the location of the police station and hospital in the area of ​​sidoarjo. In this Study, researchers make automatic geographic information system for searching the location of the hospital and police stations based on android.